The Writer's handbook - Abbe, Elfrieda; Burack, A. S. (Abraham Saul), 1908-; Houghton, Samuel G. (Samuel Gilbert), 1902-1975; Kamerman, Sylvia E.; Olsen, Udia G. (Writer, Inc., 1984)
"Manuscript market section", ed. by U.G. Olsen, 1941-44; by E.P. Werby, 1945-.